2023
DOI: 10.1177/03000605231177191
|View full text |Cite
|
Sign up to set email alerts
|

PPAR-alpha/gamma agonists, glucagon-like peptide-1 receptor agonists and metformin for non-alcoholic fatty liver disease: A network meta-analysis

Abstract: Objective To undertake a network meta-analysis to compare the relative efficacy of a dual peroxisome proliferator-activated receptor (PPAR)α and PPARγ agonist, glucagon-like peptide-1 receptor agonists (GLP-1RAs) and metformin in patients with non-alcoholic fatty liver disease (NAFLD). Methods Electronic databases, including Embase®, PubMed® and The Cochrane Library, were searched systematically for eligible studies from inception to 20 July 2022. Randomized controlled trials (RCTs) that investigated aspartate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…However, GM-CSF has been controversial in treating ALS with mixed clinical findings showing that GM-CSF might not be important to ALS patients or at least not slow down the disease process (Mortada et al, 2021). Other drugs targeting PPAR-γ and GLP-1 have also been described for their neuroprotective and anti-neuroinflammatory actions besides GM-CSF (Zhang Z. et al, 2023). Modern research suggests that molecules might relieve AD and PD symptoms, by restoring Akt-1 and mTOR, and insulin Pathways in the brain.…”
Section: Inflammatory Targetsmentioning
confidence: 99%
“…However, GM-CSF has been controversial in treating ALS with mixed clinical findings showing that GM-CSF might not be important to ALS patients or at least not slow down the disease process (Mortada et al, 2021). Other drugs targeting PPAR-γ and GLP-1 have also been described for their neuroprotective and anti-neuroinflammatory actions besides GM-CSF (Zhang Z. et al, 2023). Modern research suggests that molecules might relieve AD and PD symptoms, by restoring Akt-1 and mTOR, and insulin Pathways in the brain.…”
Section: Inflammatory Targetsmentioning
confidence: 99%
“…The exploration of thyromimetics, which mimic thyroid hormone actions to regulate metabolism, demonstrates potential in ameliorating MASH-related liver damage, inflammation, and fibrosis, as evidenced by clinical trials with agents like resmetirom ( Sinha et al, 2020 ). Similarly, agents targeting metabolic pathways, such as GLP-1 receptor agonists and PPARα agonists, are under investigation for their capacity to correct metabolic abnormalities integral to MASH pathophysiology ( Zhu et al, 2021 ; Zhang et al, 2023 ). Moreover, the complex interplay between MASH and gut microbiota suggests that modulating the gut microbiome through probiotics, prebiotics, or faecal microbiota transplantation could offer a novel avenue for treatment, addressing dysbiosis and its contributions to liver inflammation and damage ( Xiang et al, 2022 ; Solanki et al, 2023 ).…”
Section: Multidisciplinary and Innovative Therapeutic Strategies For ...mentioning
confidence: 99%
“…A recent meta-analysis of ten clinical studies demonstrated that the treatment with saroglitazar (4 mg/day; either monotherapy or in combination) could significantly improve liver enzyme levels, reduce liver stiffness, and improve metabolic parameters (serum glucose and lipid profile) in patients with NAFLD or NASH [ 54 ]. Another recent network meta-analysis of 22 randomized controlled studies revealed that saroglitazar was significantly superior to the GLP-1 receptor agonists, including semaglutide, in improving ALT levels [ 55 ]. Overall, saroglitazar may be equal to or more effective than semaglutide for treating NASH.…”
Section: Future Prospects Of Ppar Agonists For Nafld/nashmentioning
confidence: 99%